Evaluation of the stability of precipitated uranyl peroxide and its storage characteristics in solution. Issue 2 (1st February 2016) - Kim, Kwang-Wook; Lee, Keun-Young; Baek, Ye-Ji; Chung, Dong-Yong; Lee, Eil-Hee; Moon, Jei-Kwon
Abstract : This work studied the stability of uranyl peroxide, which can be obtained as the final product of several processes to treat uranium mixture waste and uranium ore, in solution using various temperature, pH, and ionic strength conditions. The change in concentration of dissolved uranium and hydrogen peroxide from uranyl peroxide, the form of the dissolved uranium species, and the change in morphology of dissolved uranyl peroxide were investigated for 100 or more days. Uranyl peroxide was stable in distilled water at elevated temperatures, but dissolved in other solutions at temperatures higher than 40 °C; a greater amount of uranyl peroxide dissolved in more acidic conditions at elevated temperatures. Uranyl ions that dissolved from uranyl peroxide were able to be recovered as uranyl peroxide in the solution where the dissolution occurs by adding hydrogen peroxide. After the precipitation of uranyl peroxide, the uranyl concentration in the supernatant is low enough for the supernatant to be recycled or released into the environment. The morphologies of the partially dissolved uranyl peroxide and the re-precipitated uranyl peroxide from dissolved uranyl ions were different from that of the initial uranyl peroxide.